Development of an Automated PD-L1 Immunohistochemistry (IHC) Assay for Non–Small Cell Lung Cancer. Issue 8 (September 2015) - Phillips, Therese; Simmons, Pauline; Inzunza, Hector D.; Cogswell, John; Novotny, James; Taylor, Clive; Zhang, Xiaoling
<x xml:space="preserve">Abstract</x> Nivolumab, a fully human IgG4 programmed death 1 (PD-1) immune checkpoint inhibitor antibody, developed by Bristol-Myers Squibb Inc., has activity across non–small cell lung cancer (NSCLC) histologies and is Food and Drug Administration approved for treatment of metastatic squamous NSCLC with progression on or after platinum-based chemotherapy. PD-L1 has been investigated as a potential biomarker to predict clinical response to nivolumab in clinical settings. We report an automated PD-L1 immunohistochemistry (IHC) assay, which was developed to detect cell surface PD-L1 in formalin-fixed paraffin-embedded human tumor tissue specimens using Dako's Autostainer Link 48. The primary antibody for this assay is a rabbit monoclonal anti-human PD-L1 antibody, clone 28-8. The specificity of 28-8 for PD-L1 was demonstrated by antigen competition and genetic deletion of PD-L1 in tumor cell lines. The specificity of the PD-L1 IHC assay was further evaluated in a collection of 30 normal human tissues. The PD-L1 IHC assay was optimized for high sensitivity and precision in routine application. A pathology scoring and interpretation method specific to nivolumab clinical studies was adopted for the assay. The analytical performance of the assay was validated for application in the determination of PD-L1 status in human NSCLC specimens. The clinical application of the assay and scoring method was further validated in 3 Clinical Laboratory Improvement Amendments certified labs. The assay is currently being investigated in a variety of clinical studies for use as an in vitro diagnostic to select and stratify patients for treatment with the anti-PD-1 therapeutic antibody, nivolumab.